1978
DOI: 10.1099/00221287-106-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Anaerobic Metabolism of Trimethylamine, Dimethylamine and Methylamine in Hyphomicrobium X

Abstract: Hyphomicrobium strain x was grown on trimethylamine and dimethylamine as the sole sources of carbon and energy under both aerobic and anaerobic conditions and the enzymes involved in the metabolism of these compounds were investigated. During aerobic growth of the organism on trimethylamine, accumulation and subsequent utilization of dimethylamine was observed. When the organism was grown on trimethylamine under anaerobic conditions in the presence of nitrate, a sequential accumulation and utilization of dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…These have been described previously (Meiberg & Harder, 1978). Purification of dimethylamine dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These have been described previously (Meiberg & Harder, 1978). Purification of dimethylamine dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that during anaerobic growth of Hyphomicrobium X on trimethylamine and dimethylamine in the presence of nitrate, dimethylamine is oxidized by a dimethylamine dehydrogenase (Meiberg & Harder, 1978). The evidence indicated that this was a new enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trimethylamine may be converted to dimethylamine via trimethylamine N-oxide (Boulton, Crabbe & Large, 1974) or directly via a dehydrogenase-cataly sed reaction (Colby & Zatman, 1973. Dimethylamine may be converted to methylamine either via a monooxygenase (Eady, Jarman & Large, 1971) or via a dehydrogenase (Meiberg & Harder, 1976). Methylamine oxidation may proceed directly (Eady & Large, I 97 I) or via N-methylglutamate (Hersh, Peterson & Thompson, 1971 ;Bamforth & Large, 1977) and/or N-methylalanine (Lin & Wagner, 1975.…”
Section: Introductionmentioning
confidence: 99%